Editors' Choice—Growth of Layered WS2 Electrocatalysts for Highly Efficient Hydrogen Production Reaction. (17th August 2016) - Alsabban, Merfat M.; Min, Shixiong; Hedhili, M. N.; Ming, Jun; Li, Lain-Jong; Huang, Kuo-Wei
Abstract : Seeking more economical alternative electrocatalysts without sacrificing much in performance to replace precious metal Pt is one of the major research topics in hydrogen evolution reactions (HER). Tungsten disulfide (WS2 ) has been recognized as a promising substitute for Pt owing to its high efficiency and low-cost. Since most existing works adopt solution-synthesized WS2 crystallites for HER, direct growth of WS2 layered materials on conducting substrates should offer new opportunities. The growth of WS2 by the thermolysis of ammonium tetrathiotungstate (NH4 )2 WS4 was examined under various gaseous environments. Structural analysis and electrochemical studies show that the H2 S environment leads to the WS2 catalysts with superior HER performance with an extremely low overpotential (η10 = 184 mV).